Heterogeneity in asthma - Brasier, Allan R. (Advances in Experimental Medicine and Biology, 2014)
Asthma is a chronic relapsing airways disease that represents a major public health problem worldwide. Intermittent exacerbations are provoked by airway mucosal exposure to pro-inflammatory stimuli, with RNA viral infections or inhaled allergens representing the two most common precipitants. In this setting, inducible signaling pathways the airway mucosa play a central role in the initiation of airway inflammation through production of antimicrobial peptides (defensins), cytokines, chemokines and arachidonic acid metabolites that coordinate the complex processes of vascular permeability, cellular recruitment, mucous hyper-secretion, bronchial constriction and tissue remodeling.  These signals also are responsible for leukocytic infiltration into the submucosa, T helper-lymphocyte skewing, and allergic sensitization. Currently, it is well appreciated that asthma is a heterogeneous in terms of onset, exacerbants, severity, and treatment response.  Current asthma classification methods are largely descriptive and focus on a single aspect or dimension of the disease.  An active area of investigation on how to collect, use and visualize multidimensional profiling in asthma.  This book will overview multidimensional profiling strategies and visualization approaches for phenotyping asthma.  As an outcome, this work will facilitate the understanding of disease etiology, prognosis and/or therapeutic intervention.